Description of Student Responses Toward Implementation of Discovery Learning Model in Physics Learning - Darmaji Darmaji; Dwi Agus Kurniawan; Astalini Astalini; Weni Sukarni (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
The learning model is one of the strategic approaches that must be carried out by the teacher systematically and procedurally in organizing learning activities to achieve optimal learning goals. In physics, the learning process is still centered on the teacher, where the teacher still conveys the overall concept on the blackboard which is not following the 2013 curriculum that has been set. This proves that teachers who have not applied the learning model according to the demands of the 2013 curriculum This research was conducted at SMAN 08 Muaro Jambi on grade X IPA 2 students which aimed to determine student responses when given a discovery learning model during the physics learning process. The instrument used was a student questionnaire with a sample of 21 students. This research uses a mixed-method with a sequential explanatory design. Data analysis techniques use descriptive statistics to get the average value, mode, median, minimum, maximum. Based on the results of the study found that the level of student response to the learning model is categorized as good with a percentage of 61.9%.